Разорванная связь: [роман] / Чингиз Абдуллаев - Абдуллаев Чингиз (Абдуллаев, 2015)
Экземпляры: Ф 7 / В (20151124) / Инвентарный номер: 85232 / Цена: 97.27 / Сис.шифр: 84(2Рос-Рус)6-44 / Авт.знак: А-13 / ГРНТИ: 17.82 / ББК: 84(2Рос-Рус)6-44